Foreign direct investment : ownership advantages, firm specific factors, survival and performance - Ghahroudi, Mehdi; Hoshino, Yasuo; Turnbull, Stephen John (World Scientific, 2019)
"The purpose of the book is to extend and develop the literature on foreign direct investment (FDI) and multinational corporation (MNCs) subsidiaries. There are several reasons for studying foreign investment and ownership. First, firms need to identify which host country industry factors are important in choosing among the various type of equity ownership (e.g. international joint ventures or wholly-owned subsidiary). Second, international diversification through foreign market entry can provide growth and profitability at rates unavailable in home markets. A third reason this warrants some attention is that type of ownership can affect attempts to counter international competition by engaging foreign rivals on their home turf. Fourth, firms have the option of choosing the appropriate equity ownership for international markets based on balancing their resources, capabilities, and international experience with their desire for ownership and control. This book extends the literature in FDI by providing empirical support for several theories and previously defined and/or tested constructs. For example, the parent and subsidiary's factors measured in this study suggest the importance of internalization and ownership advantages of Dunning's eclectic theory."- Resumé vydavatel